Validación del comportamiento agronómico de variedades de frejol (Phaseolus vulgaris) con abono orgánico" - Díaz Patango, Luis Gabriel (2017)
In the San Juan estate of the enclosure three crowns belonging to the La Maná canton, two varieties of pigeon and forty year old pigeon bean were evaluated with two organic fertilizers (slaughterhouse and humus worm), a chemical fertilizer 10-30-10 and a low control a randomized complete block design with four replicates and four plants as an experimental unit. The variables that were evaluated were: days at flowering, germination percentage, plant height (cm), number of pods, yield per plant (g) and per plot (kg), the soil of the farm had a pH of 5.90 with a medium organic matter, medium NH4 and high phosphorus, on days at flowering the varieties bloomed at 22 and 25 days; The percentage of germination was 95%, the highest plant height at 30 days was in both varieties with the fertilizer 10-30-10 and at 40 days was with the fertilizer residue of slaughterhouses, the growth rate in the leg variety Pigeon was of negative character. The highest number of pods was presented in the palaeontological variety, with the fertilizer 10-30-10. The highest yield per plant and plot was presented in pigeon duck with worm humus. The highest benefit / cost ratio was obtained in the forty-year-old frejol plus slaughterhouse residue with 0.59 followed by pigeon pea plus worm humus with 0.50